V.4 - "Russell, Ken (ed.)" (New Delhi, 2004)
This book contains 400never before published tests, complete with a guide to assessing yourperformance. The questions you will find here are typical of those you arelikely to encounter in actual IQ tests, and provide invaluable practice foranyone who may have to take such a test in the future. By practising thedifferent types of tests and getting your mind attuned to the different types ofquestions, you can improve your IQ rating by a few vital points. So if you arefaced with an IQ test as part of a job interview, using this book could provecrucial in boosting your job prospects. It could mean the difference betweensuccess and failure!
Keywords: IQ